Disparities in food security and nutrition across climate-vulnerable regions in Bangladesh - Mahbub, Md. Jarif; Sarwar, Sneha; Ali, Masum; Alam, Md. Mahbub; Islam, Md. Mynul; Sarkar, Monishankar; Amin, Md. Ruhul (Springer, 2025)
Background In climate-vulnerable Bangladesh, certain regions are more exposed to climate-related risks. This climate vulnerability in Bangladesh exposes regional disparities, which have been overlooked in the current literature. This research addresses this gap by comparing food security and nutritional indicators in high and low-climate-vulnerable regions.